Study of the technical efficiency of the sweet chili (Capsicum chinense) in the producing regions of the Colombian Caribbean (2022)
Sweet pepper cultivation is one of the more important activities in the Caribbean region, cultivated by approximately 4,284 farmers with the family farming system, in areas ranging from 0.25 to 2.0 ha. In the literature for this region, there is no evidence of a study that has investigated the technical efficiency of this production system. For this reason, this study aimed to evaluate the technical efficiency of the use of resources by sweet chili farmers in the Caribbean producing areas of Colombia. The sample was 62 farmers, surveyed via simple random sampling from the use of statistics from the Ministry of Agriculture of Colombia. A Cobb Douglas-type functional model was formulated. The contribution of the variables seed, labor, fertilizer, weeds and yields in the productive units was determined. The results showed that labor and weed management had a positive effect on production increases. There was inefficiency with production gaps of 0.18% and efficiency of 82%; a production deficit of 1 t ha-1 was observed. There were returns on an increasing scale that was explained by the direct relationship between the inputs of labor and weed management.